Characteristics of Vegetables Following Growth-Promoting Bacteria Applications as an Environmentally Friendly Cultivation Innovation - Triani, I Gusti Ayu Lani; Soemarno, .; Rahardjo, Bambang Tri; Zubaidah, Elok (KnE Life Sciences, 2022)
The focus of this research was to determine how plant growth-promoting rhizobacteria (PGPR) can affect the soil and physical characteristics of Chinese cabbages, tomatoes, and carrots. A two-factor randomized block design was used. The first factor examined was the time spent soaking the seeds in PGPR solution and the alternatives tested were 0, 10, 20, or 30 minutes. The second factor was the PGPR concentration used when watering the plants in the beds and the alternatives tested were 0, 1.25, 2.5, or 3.75 cc/L. The study found that using PGPR had an effect on soil organic matter and NPK levels, plant height, and yields that differed slightly from the characteristics obtained through conventional practices. The texture and brightness of the Chinese cabbages, tomatoes, and carrots were affected by PGPR treatment. The average texture of the Chinese cabbages, tomatoes, and carrots from the PGPR application was 23.46, 22.82, and 34.14 kg m/sec2, respectively, with brightness levels of 40.19, 34.06, and 39.10. The Chinese cabbages, tomatoes, and carrots from conventional farming practices had textures of 27.12, 23.03, and 31.13 kg m/sec2, respectively, and brightness levels of 58.11, 34.16, and 43.04. The texture and brightness level of the Chinese cabbages, tomatoes, and carrots produced by PGPR application were nearly identical to those produced by conventional farming practices. Keywords: plant growth-promoting rhizobacteria, characteristics, Chinese cabbages, tomatoes, and carrots